Mitigasi Hukum Pemerintah Daerah Provinsi Nanggroe Aceh Darussalam pada Krisis Pengungsian Etnis Rohingya dalam Rangka Menjaga Wilayah Pertahanan Negara - Tetty Melina Lubis; Arief Fahmi Lubis; Parluhutan Sagala; Tiarsen Buaton (Pusat Riset dan Inovasi Nasional, 2023)
This article discusses the legal mitigation efforts of the Nanggroe Aceh Darussalam provincial government in response to the Rohingya refugee crisis. The crisis poses a threat to national defense and security, and the government must take legal measures to mitigate its impact. The article examines the legal strategies employed by the government to address the crisis and protect the nation's territorial defense.